Preparation method and application of black titanium dioxide composite material with low refractive index

By increasing the proportion of trivalent titanium in black titanium dioxide, making it porous, and recombining it with nano SiO2, the problem of excessive refractive index of black titanium dioxide is solved, and black titanium dioxide with low refractive index, excellent photocatalytic and antistatic properties is achieved Composite material.

CN119432129APending Publication Date: 2025-02-14TIANJIN VOCATIONAL INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411568018.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The refractive index of existing black titanium dioxide materials in the solar spectrum region is too high, affecting its application as a glass photocatalytic self-cleaning anti-reflection and impermeability coating material.

Method used

By increasing the proportion of trivalent titanium in black titanium dioxide, making it porous, and compounding it with nano SiO2, diethanolamine titanium complex and silicon powder reduction reaction were used, combined with ion exchange method and high-temperature roasting, a low-refractive index black titanium dioxide composite was prepared. Material.

Benefits of technology

The refractive index and resistivity of the black titanium dioxide composite material are significantly reduced, its photocatalytic activity and antistatic properties are improved, and its anti-reflection and enhancement properties to sunlight are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a low-refractive-index black titanium dioxide composite material. The preparation method comprises the following steps: reducing a tetravalent titanium complex by using silicon powder in an alkaline ethanol water solution to prepare a black titanium dioxide and nano SiO2 composite material; the refractive index of the black titanium dioxide composite material is synergistically reduced by increasing the proportion of trivalent titanium in black titanium dioxide, enabling the black titanium dioxide to be porous and compositing with nano SiO2, the obtained black titanium dioxide composite material powder comprises, by mass, 25%-45% of SiO2, 20%-50% of TiO2 and 20%-40% of Ti2O3, the refractive index is 1.7-1.9, the particle size is 20-100 nm, and the particle size is 20-100 nm. And the specific surface area is 260-600m < 2 > / g. The black titanium dioxide composite material powder is further dispersed in acidic nanometer SiO2 ethanol hydrosol to prepare glass coating liquid, the glass is coated with the glass coating liquid in a single face mode, high-temperature sintering is conducted after drying is conducted, and the photocatalytic self-cleaning anti-reflection anti-reflection coated glass is obtained, the sunlight light transmittance of the photocatalytic self-cleaning anti-reflection anti-reflection coated glass is 93.6%-94.6%, the surface square resistance of the photocatalytic self-cleaning anti-reflection anti-reflection coated glass is 105-107 ohms, and the photocatalytic self-cleaning anti-reflection anti-reflection coated glass is the surface water contact angle of the coating layer is 3-5 degrees, and the coating layer comprises the following components in percentage by mass: 50%-75% of SiO2, 10%-25% of TiO2 and 10%-30% of Ti2O3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a low-refractive-index black titanium dioxide composite material, belonging to the technical field of new materials and photocatalysis. Background Art

[0002] Silicon solar cells and solar thermal collectors are in urgent need of a low-refractive-index self-cleaning anti-reflection and anti-reflection coated glass as a cover plate. The technical requirements are as follows: (1) It has a good anti-reflection and anti-reflection effect on sunlight; (2) It has antistatic properties and can reduce the adsorption of dust on the glass surface; (3) It has the function of photocatalytic degradation of organic pollutants and can effectively degrade organic pollutants on the glass surface; (4) It has super hydrophilicity and can make water mist spread quickly into a thin film on the glass surface to prevent water droplets from reflecting and blocking sunlight; (5) It has high hardness, wear resistance, resistance to artificial water cleaning, and can be used for a long time in a humid and hot climate environment.

[0003] Black titanium dioxide is a non-stoichiometric titanium oxide containing low-valent titanium. Its chemical composition can be expressed as TiO 2-x , where 0<x<2. Unlike traditional white TiO2 which can only absorb ultraviolet light, black titanium dioxide can absorb visible light of different wavelengths, so its surface is black.

[0004] Black titanium dioxide differs from traditional white TiO2 not only in appearance color, but also in chemical composition, crystal structure, electrical properties and optical properties. It can be used in self-cleaning coatings, cosmetics, product coloring, photocatalysis, water decomposition to produce hydrogen, organic pollutant degradation, photoelectric conversion and photothermal conversion.

[0005] There are four main methods for preparing black titanium dioxide in terms of principle and practice: (1) 4+ The ions are not completely reduced, and the trivalent titanium Ti is generated. 3+ Self-doping into TiO2 to form a chemical composition of TiO 2-x black titanium dioxide, wherein 0<x<2; (2) partially removing some oxygen atoms in white TiO2 to form oxygen vacancies, forming a chemical composition of TiO 2-x black titanium dioxide, wherein 0<x<2; (3) Ti 0 、Ti 2+ or Ti 3+ Low-valent titanium compounds are incompletely oxidized to form a chemical composition of TiO 2-x black titanium dioxide, wherein 0<x<2; (4) selective combination of the above three pathways to form a black titanium dioxide having a chemical composition of TiO 2-x Black titanium dioxide, wherein 0<x<2.

[0006] The early reported method for preparing black titanium dioxide mainly used white TiO2 as raw material and prepared it by high-temperature thermal reduction in a high-pressure hydrogen atmosphere. Later, various chemical reducing agents or physical reduction methods were invented to replace hydrogen to reduce tetravalent titanium to trivalent titanium, making the preparation process of black titanium dioxide simpler, easier, safer and more reliable.

[0007] For example, patent CN111675240B discloses a black titanium dioxide and its preparation method and application. Tetrabutyl titanate, acetic acid and titanium powder are uniformly mixed and subjected to hydrothermal reaction. During the hydrothermal reaction, the titanium powder reduces part of the titanium in TiO2 to obtain titanium dioxide doped with trivalent titanium, i.e. black titanium dioxide. The preparation method is simple and easy, and has low energy consumption. The obtained black titanium dioxide has good catalytic performance under visible light.

[0008] Patent CN104941614B discloses a method for preparing black titanium dioxide by contact reduction, including solid and liquid contact reduction methods. Under negative pressure or in an inert atmosphere, a mixture of a reducing agent and TiO2 is heated to 200-800°C, maintained for a specified time, and TiO2 is reduced to obtain black titanium dioxide; or TiO2 is dispersed in water, a reducing agent is added to the water in which TiO2 is dispersed, stirred for a specified time, and reduced to obtain black titanium dioxide, wherein the reducing agent is a metal hydride, a metal borohydride, and / or a highly active metal.

[0009] Patent CN 111960464B discloses a titanium dioxide nanomaterial rich in oxygen vacancy defects and its preparation method and application. The method combines sol-gel with solid-phase synthesis, dissolves a soluble titanium salt and adds an alkaline solution to obtain a precipitate; then the precipitate reacts with a reducing agent to obtain a titanium dioxide precursor gel with negatively charged groups; the titanium dioxide precursor gel with negatively charged groups is sintered in an inert gas to obtain a pure titanium dioxide nanomaterial rich in oxygen vacancy defects. The obtained titanium dioxide nanomaterial rich in oxygen vacancy defects has an oxygen vacancy content of 8% and an energy band gap of 1.94 eV, which has higher photocatalytic activity than other titanium dioxides.

[0010] Patent CN1071289694A discloses a method for preparing and applying a coating material that makes glass have a self-cleaning effect. During the preparation, a hydrogen peroxide solution is added to titanium hydride powder, and then water is added and stirred to obtain a yellow colloidal product; the polytetrafluoroethylene liner of the hydrothermal reactor is pretreated, and then the yellow colloidal product mixture and additives are placed in the polytetrafluoroethylene liner, and the polytetrafluoroethylene liner is placed in a matching titanium sleeve and tightened; the hydrothermal reactor is placed in a constant temperature reactor to react to obtain black TiO2 powder; vacuum filtration is performed to obtain the finished product. The present invention produces a coating material with uniform particle size, good stability, high surface -OH, internal oxygen vacancies or Ti 3+The preparation method is simple, the preparation time is short, and it is easy to accurately control. The black titanium dioxide particles produced are ultra-thin flaky anatase phase or rutile phase with a thickness of only 1-10 nanometers. They can be tightly combined with the glass surface, and their ultra-thin characteristics do not affect the light transmittance.

[0011] Most of the existing technologies use contact reduction to prepare black titanium dioxide, in which the molar content of trivalent titanium compound is less than 30% of the total molar content of titanium. 4+ Reduction reaction and Ti 3+ The self-doping is carried out on the surface of titanium dioxide particles. The product has an amorphous black titanium dioxide shell, and the core is still unreduced high-refractive-index titanium dioxide. Therefore, the surface photocatalytic activity of black titanium dioxide has changed significantly compared with traditional white titanium dioxide. However, the problems of poor overall conductivity and high refractive index of the material still exist, which affects its application as a glass photocatalytic self-cleaning anti-reflection and anti-reflection coating material.

[0012] The new black titanium dioxide material is an upgraded product of the traditional white titanium dioxide. It has good photocatalytic activity in the entire solar spectrum, and has good antistatic, high hardness, wear resistance and resistance to moisture and heat erosion. Its only drawback is that its refractive index or reflectivity to sunlight is too high, which will significantly reduce the transmittance of coated glass in application. The most commonly used method to reduce the refractive index of a material is to form a composite material with a low refractive index material. Through the composite material method, the defect of the high refractive index of black titanium dioxide is also overcome, making it the most promising photocatalytic self-cleaning anti-reflection and anti-reflection glass coating material. Summary of the invention

[0013] The purpose of the present invention is to provide a method for preparing a low-refractive index black titanium dioxide composite material, which reduces the refractive index of the black titanium dioxide composite material in a coordinated manner by increasing the proportion of trivalent titanium in the black titanium dioxide, making the black titanium dioxide porous, and compounding with nano-SiO2. The method comprises five parts: preparing a diethanolamine titanium complex ethanol hydrosol S1, preparing a black titanium dioxide precursor and a nano-SiO2 precursor mixed ethanol hydrosol S2, removing alkali metal ions in the mixed ethanol hydrosol S3 by an ion exchange method, gelling the mixed ethanol hydrosol S4, and forming a low-refractive index black titanium dioxide composite material S5. The specific operation steps are as follows:

[0014] S1: adding a diethanolamine solution to an ethanol aqueous solution having an ethanol mass fraction of 70% to 90%, and adding tetrabutyl titanate under stirring to form a translucent diethanolamine titanium yellow ethanol hydrosol by complexing with the diethanolamine;

[0015] S2: adding an alkali metal salt catalyst to the yellow ethanol hydrosol of diethanolamine titanium, adding silicon powder in an air-tight condition to initiate a reduction reaction, observing that hydrogen is slowly released from the surface of the silicon powder, controlling the temperature of the reaction liquid to 30-60° C., adding silicon powder in batches, reducing more than 35% of the tetravalent titanium in the diethanolamine titanium to trivalent titanium, and generating a mixed ethanol hydrosol of a black titanium dioxide precursor and a nano-SiO2 precursor; the alkali metal salt catalyst is one of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium silicate, sodium silicate, potassium silicate or a mixture thereof;

[0016] S3: adding a strongly acidic cation exchange resin to the reduction reaction solution, stirring for 0.5-2h, and adsorbing the alkali metal ions in the reduction reaction solution; when the pH of the reduction reaction solution is 7-8, the adsorption and exchange of the alkali metal ions is completed, filtering and separating the strongly acidic cation exchange resin, and obtaining a mixed ethanol hydrosol of a black titanium dioxide precursor and a nano-SiO2 precursor without alkali metal ions;

[0017] S4: adding a dilute inorganic acid solution to the mixed ethanol hydrosol of the black titanium dioxide precursor and the nano-SiO2 precursor without alkali metal ions, adjusting the pH of the mixed hydrosol to 4-6, and forming a mixture gel of the black titanium dioxide precursor and the nano-SiO2 precursor, wherein the inorganic acid is one of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid or a mixture thereof;

[0018] S5: drying the mixture gel of the black titanium dioxide precursor and the nano-SiO2 precursor at 100-150° C., and further calcining in an air-tight state at 450-650° C. for 1-6 hours to obtain a low refractive index black titanium dioxide composite material powder.

[0019] In step S1, during the precipitation and dissolution reaction, the molar ratio of the feed is controlled to be Ti: diethanolamine = 1:2-3 to obtain an ethanol hydrosol of the diethanolamine titanium complex.

[0020] The molar ratio of the materials in the reduction reaction of step S2 is Ti:Si:alkali metal salt=1:0.5-1.5:0.04-0.1, so that more than 35% of the total molar number of titanium is reduced to trivalent titanium.

[0021] Step S5 obtains a low refractive index black titanium dioxide nano-SiO2 composite material powder having a mass composition of SiO2 25%-45%, TiO2 20%-50%, Ti2O3 20%-40%, a refractive index of 1.7-1.9, a particle size of 20-100nm, and a specific surface area of ​​260-600m 2 / g.

[0022] The present invention uses tetrabutyl titanate as a titanium source, which is easily hydrolyzed to form insoluble white nano titanium dioxide. When silicon powder is used to reduce the nano titanium dioxide suspension, the conversion rate of the nano titanium dioxide is very low. The present invention utilizes the property that tetrabutyl titanate can form a water-soluble complex with diethanolamine, and diethanolamine is added to prepare a water-soluble diethanolamine titanium complex, thereby improving the efficiency of reducing to form trivalent titanium.

[0023] In the present invention, tetrabutyl titanate and diethanolamine titanium complex, whether tetravalent titanium or trivalent titanium, are collectively referred to as black titanium dioxide precursors, because they are transformed into black titanium dioxide after high-temperature treatment.

[0024] In the present invention, silicon powder is used as a reducing agent for preparing black titanium dioxide, which has the advantages of being cheap and readily available, and the byproduct nano silicon dioxide can also be fully utilized. The principle of the reduction reaction is that silicon powder can incompletely reduce tetravalent titanium or its complex to trivalent titanium under alkaline conditions, and the generated trivalent titanium compound can be self-doped into the titanium dioxide precursor to further form black titanium dioxide; and silicon powder is oxidized to metasilicic acid, alkali metal metasilicate and metasilicic acid oligomers, which are dehydrated to generate nano SiO2, which is generally referred to as a silicon dioxide precursor in the present invention, and the chemical reaction formula is expressed as:

[0025] 4Ti 4+ +Si+4OH - →4Ti 3+ +H2SiO3+H2O

[0026] 2Si+4H2O+2OH - →H2SiO3+SiO3 2- +4H2↑

[0027] The reduction reaction rate of silicon powder in neutral ethanol aqueous solution is very slow. After adding alkali metal hydroxide or alkali metal silicate catalyst, the dissolution of silicon powder and hydrogen evolution reaction are very fast. It is necessary to control the feeding rate of silicon powder and the reaction temperature to reduce the hydrogen evolution rate and improve the reaction selectivity of generating trivalent titanium compounds.

[0028] In the present invention, an excessive amount of silicon powder reducing agent is added to reduce more than 35% of the total titanium to trivalent titanium compounds, so that the photocatalytic performance, anti-reflection and anti-transmittance performance and antistatic performance of black titanium dioxide are improved simultaneously. Studies have found that the photocatalytic activity of the black titanium dioxide and silicon dioxide composite material is more than 50% higher than that of pure black titanium dioxide, and the refractive index or reflectivity is greatly reduced. It can be seen that the excess silicon powder in the reduction reaction is not wasted, but is used to generate nano-SiO2. Experiments have found that the particles of the black titanium dioxide and silicon dioxide composite material have a core-shell structure, the core is nano-silicon dioxide, and the shell is black titanium dioxide. The composite of black titanium dioxide and silicon dioxide not only increases the specific surface area of ​​the black titanium dioxide in the shell and improves the antistatic performance, but also greatly reduces the refractive index of the composite material. When the titanium-silicon molar ratio is 1:0.4-1, the black titanium dioxide and silicon dioxide composite material has the best comprehensive performance such as photocatalytic self-cleaning performance, antistatic dust absorption and anti-reflection and anti-transmittance.

[0029] Because black titanium dioxide is an amphoteric oxide, if alkali metal ions are doped into it, its acidity and alkalinity will change and the photocatalytic efficiency will be greatly reduced. In the present invention, a strong acid cation exchange resin is used to efficiently remove the alkali metal ions in the reduction reaction completion liquid. When the strong acid cation exchange resin is adsorbed and exchanged to the pH of the reduction reaction completion liquid = 7-8, the alkali metal ions are completely adsorbed. The alkali metal ions can be completely removed along with the strong acid cation exchange resin by simply filtering the saturated adsorbed strong acid cation exchange resin.

[0030] The nano-SiO2 precursor aqueous sol generated in the reduction reaction of the present invention is relatively stable under alkaline conditions. When a small amount of nitric acid, sulfuric acid, hydrochloric acid or phosphoric acid dilute solution is added thereto to adjust the pH of the nano-SiO2 precursor aqueous sol to 4-6, the nano-SiO2 precursor aqueous sol, together with the black titanium dioxide precursor therein, becomes a mixed gel of nano-SiO2 precursor-black titanium dioxide precursor.

[0031] The ethanol-water solution in the mixture gel evaporates slowly naturally. When heated to above 100°C in an oven, the drying speed of the mixture gel is greatly increased. After the mixture gel is dried, the nano-SiO2 precursor is dehydrated to become nano-SiO2, and the precursor mixture of trivalent titanium and tetravalent titanium is coated on the nano-SiO2 and converted into black titanium dioxide.

[0032] During the high-temperature calcination process in an air-tight state, the diethanolamine ligand combined with the black titanium dioxide precursor volatilizes and decomposes at high temperature, and trivalent titanium is self-doped into tetravalent titanium oxide to form a porous black titanium dioxide and nano-silicon dioxide composite material. The volatilization and complete decomposition of the diethanolamine ligand leave a large number of micropores, forming a porous black titanium dioxide composite material, further increasing the specific surface area of ​​the black titanium dioxide composite material and reducing the refractive index of the black titanium dioxide composite material. Because the refractive index of the air adsorbed in the micropores of the porous black titanium dioxide composite material is 1, the refractive index of nano-SiO2 is 1.5, the refractive index of nano-Ti2O3 is 1.5, and the refractive index of nano-TiO2 is 2.3, the composite of nano-TiO2 with air, SiO2 and Ti2O3 can reduce the refractive index of the black titanium dioxide composite material.

[0033] In addition, during the high-temperature calcination process in an airtight environment, the trivalent titanium compound is converted into β-Ti2O3, which gives the black titanium dioxide composite material good antistatic properties. Because the trivalent titanium oxide α-Ti2O3 is converted into β-Ti2O3 at high temperatures, it is a conductive conductor that can significantly reduce the resistivity of the black titanium dioxide composite material.

[0034] Compared with the prior art, the preparation method of the low refractive index black titanium dioxide composite material of the present invention has outstanding substantial characteristics and significant technical progress in the following aspects: (1) the silicon powder reducing agent is cheap and easy to obtain, safe and environmentally friendly, and has industrial application prospects; (2) the reducing agent byproduct nano-SiO2 is used as the crystal nucleus for generating black titanium dioxide, which not only expands the specific surface area of ​​black titanium dioxide, but also synergistically improves the photocatalytic performance of the composite material; (3) more than 35% of the total titanium in the black titanium dioxide is Ti2O3, which can significantly reduce the refractive index and resistivity of the material; (4) the diethanolamine ligand used dissolves the titanium dioxide precursor, greatly improving the conversion rate of tetravalent titanium reduction to trivalent titanium; (5) the high-temperature volatilization and decomposition of the diethanolamine ligand create conditions for preparing a porous low refractive index black titanium dioxide composite material; (6) the low refractive index black titanium dioxide composite material responds to the entire solar spectrum, greatly reduces the reflection of sunlight, and is particularly suitable as a self-cleaning anti-reflection and anti-reflection coating material for solar glass.

[0035] Another object of the present invention is to provide an application method of a low-refractive-index black titanium dioxide composite material, which mainly comprises five parts: preparation of a black titanium dioxide composite material coating liquid T1, coating the black titanium dioxide composite material coating liquid on glass T2, drying the black titanium dioxide composite material coating layer T3, sintering the black titanium dioxide composite material coating layer T4, and performance testing of the black titanium dioxide composite material coating layer T5. The specific operation steps are as follows:

[0036] T1: dissolving ethyl orthosilicate in an ethanol aqueous solution with a mass fraction of 70%-90%, adding a dilute nitric acid catalyst, hydrolyzing to form a nano-SiO2 acidic ethanol hydrosol with a SiO2 mass fraction of 3%-5%; then adding black titanium dioxide composite material powder, ultrasonically dispersing, and obtaining a black titanium dioxide composite material coating solution with a solid mass fraction of 5%-10%;

[0037] T2: Apply the black titanium dioxide composite coating liquid evenly on the solar glass or ordinary glass slide, and control the thickness of the wet film to 1-2μ;

[0038] T3: Place the coated solar glass or ordinary glass sample in an oven and dry it at 100°C to form a coated glass with a dry film thickness of 100-200nm;

[0039] T4: Place the above coated glass sample in a high temperature furnace and heat it at 500-750℃ for 0.5-1h to sinter the coating layer on the surface of the glass sample. After cooling, a low refractive index black titanium dioxide composite coated glass is obtained, and its mass composition is: SiO2 50%-75%, TiO2 10%-25%, Ti2O3 10%-30%, with good photocatalytic self-cleaning anti-reflection and anti-reflection properties;

[0040] T5: The transmittance of the coated glass in the wavelength range of 200-1200nm is 93.6%-94.6%, and the surface square resistance is The water contact angle of the film surface is 3-5°, and it has anti-reflection, wear resistance, anti-static and self-cleaning functions. It can not only improve the light transmittance of the glass, but also significantly reduce the accumulation of dust and organic pollutants on the surface of the coated glass.

[0041] The nanometer particle size of the acidic nano-SiO2 ethanol hydrosol obtained by acid hydrolysis of tetraethyl orthosilicate in the present invention is only 5nm, so it has good adhesion on the glass surface. In the prior art, it is often selected as an adhesive to prepare glass anti-reflection coating liquid with alkaline nano-SiO2 hydrosol with a particle size of 20-50nm, and its good wear resistance and weather resistance have been confirmed in industrial applications.

[0042] The present invention utilizes the excellent adhesion of acidic nano-SiO2 hydrosol and selects it as an adhesive to prepare a glass self-cleaning anti-reflection coating liquid with a black titanium dioxide composite material powder with a particle size of 20-100nm. When the ethanol content in the coating liquid is relatively low, a small amount of surfactant can be added to improve the wettability of the glass surface and the flatness of the coating.

[0043] The difference between the glass coating liquid of the present invention and the existing glass anti-reflection and anti-fouling coating liquid is that a low-refractive index black titanium dioxide composite material component is added, so that the coating layer has increased anti-static dust adsorption and visible light catalytic self-cleaning properties, and retains the anti-reflection function of the original coating liquid.

[0044] Glass surface coating technology is relatively mature, and roller coating technology is generally used in engineering. In laboratory research and development, rod coating and spin coating technologies with similar principles are generally used, that is, a coating rod is used to coat a layer of coating liquid aqueous sol with a dry film thickness of 100-200nm on the glass surface. When the dry film thickness is 1 / 4 of the wavelength of visible light, the visible light reflection in sunlight is minimized or the light transmittance is maximized.

[0045] Although the acidic nano-SiO2 film has a high adhesion on the glass surface, the film layer has poor hardness and wear resistance, and is not resistant to erosion in a hot and humid environment. In engineering coated glass and laboratories, the coated glass is heated to the softening temperature of 550-650℃, and then quickly cooled to temper the glass. At the same time, the coating layer is sintered on the glass surface, which can not only improve the hardness, wear resistance and hot and humid corrosion resistance of the coating layer, but also make Ti 3+ The doping is more uniform, and the composite with nano-SiO2 is more uniform, which can improve the photocatalytic performance of the coating layer.

[0046] The coating layer of the present invention comprises SiO2 50%-75%, TiO2 10%-25%, and Ti2O3 10%-30%. Since it contains 50%-75% of SiO2 with a refractive index of 1.5 and 10%-30% of Ti2O3 with a refractive index of 1.7, the content of high-refractive-index TiO2 in the coating layer is greatly reduced, thereby greatly improving the sunlight anti-reflection and anti-transmittance performance of the coated glass.

[0047] When the volatile ethanol content in the coating solution is too low, the wet film layer takes a long time to dry at room temperature. In industry and laboratories, a heating kiln at 100-150°C is used to quickly dry and solidify the coated wet film layer. The transmittance of solar glass and ordinary glass slides in the range of 200-1200nm of sunlight wavelength is 91.6%; the square resistance of the glass surface The surface contact angle between glass and water is 30-40°. The solar transmittance of the coated glass of the present invention is 93.6%-94.6%, and the solar transmittance is increased by 2%-3%. The surface square resistance is It is reduced by 10,000 times and has good anti-static properties; under sunlight, the surface contact angle between the coated glass and water is 3-5°, which is super hydrophilic, laying the foundation for the self-cleaning of the coated glass surface.

[0048] Compared with the prior art, the application method of the low-refractive-index black titanium dioxide composite material of the present invention has outstanding substantive features and remarkable technical progress in the following aspects: (1) the low-refractive-index black titanium dioxide composite material is used as a solar glass coating material; (2) the problem of the conflict between the anti-reflection and anti-transmittance functions and the photocatalytic self-cleaning functions of the coated glass is solved; (3) the black titanium dioxide composite material coated glass has good photocatalytic self-cleaning functions under sunlight; (4) the surface of the black titanium dioxide coated glass is hard, wear-resistant, anti-static and resistant to moisture and heat erosion, and is expected to become an upgraded product of the existing coated glass.

[0049] The beneficial effects of the present invention are embodied in:

[0050] (1) The silicon powder reducing agent used in the present invention is cheap and easy to obtain, and the by-product nano-SiO2 can be fully utilized to improve the performance of the composite material, which has industrial application prospects;

[0051] (2) The combination of black titanium dioxide and nano-silicon dioxide not only synergistically improves the photocatalytic self-cleaning performance of the black titanium dioxide composite material, but also significantly reduces the refractive index and resistivity of the black titanium dioxide composite material; (3) The low-refractive-index black titanium dioxide composite material responds to the entire solar spectrum and significantly reduces the reflection of sunlight, making it particularly suitable as a self-cleaning anti-reflection and anti-reflection coating material for solar glass. DETAILED DESCRIPTION

[0052] Example 1

[0053] To 200g of 90% ethanol aqueous solution, add 21g (0.2mol) of diethanolamine solution under stirring, add 34g (0.1mol) of tetrabutyl titanate under air isolation and stirring to form a translucent diethanolamine titanium yellow ethanol hydrosol, then add 0.4g (0.01mol) of sodium hydroxide catalyst, and then add silicon powder to initiate a reduction reaction, hydrogen is slowly released, the temperature of the reaction liquid is controlled to 30-60°C, and a total of 2.8g (0.1mol) of silicon powder is added in batches, and it is measured that 65% of the tetravalent titanium in the diethanolamine titanium is reduced to trivalent titanium, and 257g of a mixed hydrosol of a black titanium dioxide precursor and a nano-SiO2 precursor is reduced to generate; a strongly acidic cation exchange resin is added to the reduction reaction completed liquid; 5g, stirred for 0.5h, filtered and separated with strongly acidic cation exchange resin, and obtained 250g of alkali metal ion-free black titanium dioxide precursor and nano-SiO2 precursor mixed ethanol hydrosol; added dilute nitric acid solution thereto, adjusted the pH of the mixed hydrosol to 4-6, and formed a mixture gel of black titanium dioxide precursor and nano-SiO2 precursor; dried the mixture gel at 100-150°C, and further calcined at 650°C in air-tight condition for 1h, and obtained 13.48g of low-refractive-index black titanium dioxide and nano-SiO2 composite material powder, whose mass composition was: SiO2 44.5%, TiO2 20.8%, Ti2O3 34.7%; refractive index was 1.7, particle size was 20-100nm, and specific surface area was 510m 2 / g.

[0054] Example 2

[0055] A low-refractive-index black titanium dioxide composite material was prepared in the manner of Example 1, except that the depth of the reduction reaction was reduced, 1.4 g (0.05 mol) of silicon powder was added, and it was measured that 35% of the tetravalent titanium in the diethanolamine titanium was reduced to trivalent titanium. The reduction reaction generated 205 g of a mixed aqueous sol of a black titanium dioxide precursor and a nano-SiO2 precursor; 5 g of a strongly acidic cation exchange resin was added to the reduction reaction complete solution, stirred for 0.5 h, and the strongly acidic cation exchange resin was filtered to separate, to obtain a mixed aqueous sol of a black titanium dioxide precursor and a nano-SiO2 precursor free of alkali metal ions. 200g of gel; adding dilute nitric acid solution thereto, adjusting the pH of the mixed hydrosol to 4-6, forming a mixed gel of black titanium dioxide precursor and nano-SiO2 precursor; drying the mixed gel at 100-150°C, and further calcining at 450°C in air-tight condition for 2h to obtain 10.7g of low-refractive-index black titanium dioxide and nano-SiO2 composite powder, the mass composition of which is: SiO2 28.0%, TiO2 48.5%, Ti2O3 23.5%; the refractive index is 1.9, the particle size is 20-100nm, and the specific surface area is 350m 2 / g.

[0056] Example 3

[0057] Dissolve 20.8g (0.1mol) of tetraethyl orthosilicate in 90% ethanol aqueous solution, add a small amount of dilute nitric acid catalyst, place for 12h, hydrolyze to form 120g of nano-SiO2 acidic ethanol hydrosol with SiO2 mass fraction of 5%; then add 6g of black titanium dioxide composite material powder obtained in Example 1, ultrasonically disperse, and obtain 126g of black titanium dioxide composite material coating liquid with solid mass fraction of 9.5%. Use a coating rod to evenly coat it on an ordinary glass slide, control the wet film thickness to be 1-2μ; place it in an oven and dry it at 100℃ to form a coated glass with a dry film thickness of 100-200nm; place the above coated glass sample in a high-temperature furnace, heat it at 650℃ for 0.5h, sinter the coating layer on the surface of the glass sample, and obtain low refractive index black titanium dioxide composite material coated glass after cooling. The mass composition of the coating layer is: SiO2 72.3%, TiO2 10.4%, Ti2O3 17.3%; the transmittance of the coated glass in the wavelength range of 200-1200nm is measured to be 94.1%, and the surface square resistance is The water contact angle of the film surface is 3-5°, and it has anti-reflection, wear resistance, anti-static and self-cleaning functions. It can not only improve the light transmittance of the glass, but also significantly reduce the accumulation of dust and organic pollutants on the surface of the coated glass.

[0058] Example 4

[0059] 20.8g (0.1mol) of tetraethyl orthosilicate was dissolved in an ethanol aqueous solution with a mass fraction of 90%, and a small amount of dilute nitric acid catalyst was added. After standing for 12 hours, the solution was hydrolyzed to form 120g of nano-SiO2 acidic ethanol hydrosol with a mass fraction of 5% SiO2; 6.0g of the black titanium dioxide composite material powder obtained in Example 2 was added, and ultrasonic dispersion was performed to obtain 126g of a black titanium dioxide composite material coating liquid with a solid mass fraction of 9.5%. The solution was evenly coated on an ordinary glass slide with a coating rod, and the wet film thickness was controlled to be 1-2μ; the solution was placed in an oven and dried at 100°C to form a coated glass with a dry film thickness of 100-200nm; the above coated glass sample was placed in a high-temperature furnace and heated at 450°C for 1.5 hours to sinter the coating layer on the surface of the glass sample, and low refractive index black titanium dioxide composite material coated glass was obtained after cooling. The mass composition of the coating layer is: SiO2 64.0%, TiO2 24.2%, Ti2O3 11.8%; the transmittance of the coated glass in the wavelength range of 200-1200nm is 93.6%, and the surface square resistance is The water contact angle of the membrane surface is 3-5°, and it has anti-reflection, wear resistance, anti-static and self-cleaning functions.

Claims

1. A method for preparing a low refractive index black titanium dioxide composite material, characterized in that: The refractive index of the black titanium dioxide composite material is synergistically reduced by increasing the proportion of trivalent titanium in the black titanium dioxide, making the black titanium dioxide porous, and compounding with nano-SiO2. The method comprises five parts: preparing diethanolamine titanium complex ethanol hydrosol S1, preparing black titanium dioxide precursor and nano-SiO2 precursor mixed ethanol hydrosol S2, removing alkali metal ions in the mixed ethanol hydrosol S3 by ion exchange method, gelling the mixed ethanol hydrosol S4, and forming a low-refractive-index black titanium dioxide composite material S5. The specific operation steps are as follows: S1: adding a diethanolamine solution to an ethanol aqueous solution having an ethanol mass fraction of 70% to 90%, and adding tetrabutyl titanate under stirring to form a translucent diethanolamine titanium yellow ethanol hydrosol by complexing with the diethanolamine; S2: adding an alkali metal salt catalyst to the yellow ethanol hydrosol of diethanolamine titanium, adding silicon powder in an air-tight condition to initiate a reduction reaction, observing that hydrogen is slowly released from the surface of the silicon powder, controlling the temperature of the reaction liquid to 30-60° C., adding silicon powder in batches, reducing more than 35% of the tetravalent titanium in the diethanolamine titanium to trivalent titanium, and generating a mixed ethanol hydrosol of a black titanium dioxide precursor and a nano-SiO2 precursor; the alkali metal salt catalyst is one of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium silicate, sodium silicate, potassium silicate or a mixture thereof; S3: adding a strongly acidic cation exchange resin to the reduction reaction solution, stirring for 0.5-2h, and adsorbing the alkali metal ions in the reduction reaction solution; when the pH of the reduction reaction solution is 7-8, the adsorption and exchange of the alkali metal ions is completed, filtering and separating the strongly acidic cation exchange resin, and obtaining a mixed ethanol hydrosol of a black titanium dioxide precursor and a nano-SiO2 precursor without alkali metal ions; S4: adding a dilute inorganic acid solution to the mixed ethanol hydrosol of the black titanium dioxide precursor and the nano-SiO2 precursor without alkali metal ions, adjusting the pH of the mixed hydrosol to 4-6, and forming a mixture gel of the black titanium dioxide precursor and the nano-SiO2 precursor, wherein the inorganic acid is one of nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid or a mixture thereof; S5: drying the mixture gel of the black titanium dioxide precursor and the nano-SiO2 precursor at 100-150° C., and further calcining in an air-tight state at 450-650° C. for 1-6 hours to obtain a low refractive index black titanium dioxide composite material powder.

2. The method for preparing a low refractive index black titanium dioxide composite material according to claim 1, characterized in that: Step S1: during the dissolution reaction of tetrabutyl titanate, the molar ratio of the feed is controlled to be Ti: diethanolamine = 1:2-3, and a diethanolamine titanium complex hydrosol is obtained; 3. The method for preparing a low refractive index black titanium dioxide composite material according to claim 1, characterized in that: The molar ratio of the feed materials in the reduction reaction of step S2 is Ti:Si:alkali metal salt=1:0.5-1.5:0.04-0.1, so that more than 35% of the total molar number of titanium is reduced to trivalent titanium.

4. The method for preparing a low refractive index black titanium dioxide composite material according to claim 1, characterized in that: Step S5 obtains a low refractive index black titanium dioxide nano-SiO2 composite material powder having a mass composition of SiO2 25%-45%, TiO2 20%-50%, Ti2O3 20%-40%, a refractive index of 1.7-1.9, a particle size of 20-100nm, and a specific surface area of ​​260-600m 2 / g.

5. An application method of a low refractive index black titanium dioxide composite material, characterized in that include: The five parts include preparation of black titanium dioxide composite material coating solution T1, coating of black titanium dioxide composite material coating solution on glass T2, drying of black titanium dioxide composite material coating layer T3, sintering of black titanium dioxide composite material coating layer T4 and performance testing of black titanium dioxide composite material coating layer T5. The specific operation steps are as follows: T1: dissolving ethyl orthosilicate in an ethanol aqueous solution with a mass fraction of 70%-90%, adding a dilute nitric acid catalyst, hydrolyzing to form a nano-SiO2 acidic ethanol hydrosol with a SiO2 mass fraction of 3%-5%; then adding black titanium dioxide composite material powder, ultrasonically dispersing, and obtaining a black titanium dioxide composite material coating solution with a solid mass fraction of 5%-10%; T2: Apply the black titanium dioxide composite coating liquid evenly on the solar glass or ordinary glass slide, and control the thickness of the wet film to 1-2μ; T3: Place the coated solar glass or ordinary glass sample in an oven and dry it at 100°C to form a coated glass with a dry film thickness of 100-200nm; T4: Place the above coated glass sample in a high temperature furnace and heat it at 500-750℃ for 0.5-1h to sinter the coating layer on the surface of the glass sample. After cooling, a low refractive index black titanium dioxide composite material coated glass is obtained, which has good photocatalytic self-cleaning anti-reflection and anti-reflection properties; T5: The transmittance of the coated glass in the wavelength range of 200-1200nm is 93.6%-94.6%, and the surface square resistance is The water contact angle of the film surface is 3-5°, and it has anti-reflection, wear resistance, anti-static and self-cleaning functions. It can not only improve the light transmittance of the glass, but also significantly reduce the accumulation of dust and organic pollutants on the surface of the coated glass.

6. An application method of a low refractive index black titanium dioxide composite material, characterized in that The coating layer obtained in step T4 of claim 5 has a mass composition of SiO2 50%-75%, TiO2 10%-25%, and Ti2O3 10%-30%.

Citation Information

Patent Citations

  • Method for preparing black titanium dioxide by contact reduction

    CN104941614B